Diversity in the labour market: The legal framework and support services for migrants entitled to work in the United Kingdom - Alison Hunter (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
The paper sets out the legal and regulatory framework which applies to migrants who are legally in the United Kingdom and who have the right to work for at least one year. The first section looks at the rights and restrictions conferred by immigration law which is the basis for considering whether a migrant has the right to work in the UK. The paper then goes on to look at the problems migrants face accessing work and their rights under UK employment law. It also sets out the rights in areas which are closely connected to employment, such as education. The final section reviews the provision available to migrant workers to better their work prospects. The paper argues that the legal framework of immigration law clearly favours highly skilled migrants who, however, are being given little support to access the labour market. Provision of support services is clearly concentrated on refugees and those with humanitarian or discretionary protection.
Keywords: 330